Energy Consumption Management in IoT by Load Balancing at Near-Root Nodes in RPL Protocol - Joël, ADEPO; EDI Kouassi Hilaire; BREDOU Amian Etienne; N’GORAN Niamien Thiery Michael (Engineering And Technology Journal, 2024)
Managing energy consumption in Internet of Things constitutes a challenge for researchers. Many existing works address this question. Some approaches propose solutions based on artificial intelligence. Other studies are based on improving existing routing protocols. The results obtained are promising and the energy gains recorded are remarkable. However, the majority of works in the literature propose a global optimization approach in the network to manage traffic flow. In doing so, we are led to neglect the bottlenecks especially around the convergence point. The objective of this work is to propose an improvement of RPL protocol, a popular routing protocol in Internet of Things.